Thought and behaviour in modern Japanese politics/ Edited by;Ivan Morris - "Maruyama, Masao" (New York, 1979)
Exploring the specific peculiarities of Japanese politics and the cultural patterns which underlie them, this study seeks to explain why Japanese intellectuals during World War II either blindly accepted nationalistic militarism or seemed impotent to halt its rise.
Keywords: Japan Politics and government